Determinants of self-efficacy in patients with Parkinson’s disease - Estrada-Bellmann, Ingrid; Meléndez-Flores, Jesús Daniel; Cámara-Lemarroy, Carlos Rodrigo; Castillo-Torres, Sergio Andrés (Arquivos de Neuro-Psiquiatria, 2021)
Background: Self-efficacy is the individual’s assessment of his or hers ability to complete a specific task successfully and has been closely related to self-management and quality of life in several diseases. Objective: To investigate self-efficacy in a population of Parkinson’s disease (PD) patients in Mexico and study the factors that are associated with this measure. Methods: We carried out a cross-sectional observational study involving patients with PD in an outpatient neurology clinic in Mexico, using the following instruments: Spanish version of the Chronic Disease Self-Efficacy Scale (CDSES), Quality of Life Questionnaire PDQ-8, Movement Disorders Society-Unified Parkinson's disease Rating Scale (MDS-UPDRS), Montreal Cognitive Assessment (MoCA), and Non-Motor Symptom Scale (NMSS). Clinical and demographic variables were also recorded. Results: We included 73 patients with a mean age of 65 years and most patients were male. Patients with lower CDSES scores (<7.75) had worse scores in MDS-UPDRS, NMSS, and PDQ-8 scales. CDSES scores were significantly correlated with MDS-UPDRS Part I (r=-0.497, p=<0.001), Part II (r= -0.271, p=0.020), Part III (r=-0.304, p=<0.001), PDQ-8 (r=-0.472, p=<0.001), and NMSS (r=-0.504, p=<0.001). Furthermore, when assessing the simultaneous effect of covariates associated with CDSES score, only Mood/Apathy domain of NMSS was significant (beta= -0.446, t= -3.807, p= 0.012). Conclusions: PD patients with lower self-efficacy scores had worse motor and non-motor symptomatology and quality of life. Mood/Apathy disorders were negatively associated with self-efficacy and contributed significantly to this measure.
Keywords: Parkinson Disease; Self Efficacy; Quality of Life; Mood Disorders; Cognition